1990
DOI: 10.1002/ajh.2830340107
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndromes: A study of surface markers and in vitro growth patterns

Abstract: A study of surface markers and in vitro growth in semi-solid and liquid medium was performed in 35 patients with newly diagnosed myelodysplastic syndrome (MDS). Surface markers were studied by CD34, CD13, CD14, CD15, and CD33 monoclonal antibodies. There was no strict correlation with the FAB typing, but CD34 was expressed only in refractory anemia with excess of blasts (RAEB) or RAEB in transformation (RAEB-t). CD14 was markedly positive in the 4 cases of chronic myelomonocytic leukemia. Colony-forming cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
2

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 15 publications
1
16
1
2
Order By: Relevance
“…Three reports pointed out a correlation between colony formation and specific chro mosome abnormalities [8,9,25], while two other reports did not find any relationship between these two param eters [13,26]. Our present study did not reveal any correla tion between colony formation by the three cell lines and the abnormal karyotype.…”
Section: Discussioncontrasting
confidence: 48%
“…Three reports pointed out a correlation between colony formation and specific chro mosome abnormalities [8,9,25], while two other reports did not find any relationship between these two param eters [13,26]. Our present study did not reveal any correla tion between colony formation by the three cell lines and the abnormal karyotype.…”
Section: Discussioncontrasting
confidence: 48%
“…12, 29,32,47,48 Within AML after MDS the prognostic relevance of CD34 expression has not been demonstrated yet, because no studies on this selected subgroup within AML have been performed. In this study we found a higher CD34 expression in AML after previous MDS as compared with the MDS subgroups, which is the first evidence in literature of a prognostic meaning of CD34 expression in AML-MDS.…”
Section: Expansion Of Cd34mentioning
confidence: 99%
“…[32][33][34] No clear reports can be found investigating the increased autonomic proliferation in MDS. In RAEB(t) and sAML we previously showed less overall apoptosis, especially in blasts, by using ISEL on BM biopsies.…”
Section: Expansion Of Cd34mentioning
confidence: 99%
See 2 more Smart Citations